PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA POP-UP BOOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MATERI KELILING DAN LUAS PERSEGI PANJANG - Sri Hayati; Ria Kurniasari; Hani Handayani (JESA-Jurnal Edukasi Sebelas April, 2025)
ability of students on the perimeter and area of rectangles. Researchers applied the Problem Based Learning (PBL) model assisted by pop-up book media to students' mathematical problem solving skills on the perimeter and area of rectangles. The formulation of this problem is whether there is a significant effect of using the Problem Based Learning (PBL) learning model assisted by pop-up book media on students' mathematical problem solving skills on the perimeter and area of rectangles in class V of Gudang I State Elementary School, Tanjungsari District, Sumedang Regency in the 2023/2024 academic year. The purpose of this study was to determine the effect of using the Problem Based Learning (PBL) learning model assisted by pop-up book media on students' mathematical problem solving skills on the perimeter and area of rectangles in class V SDN Gudang I. The research method used was experimental research with the help of pop-up book media. The research method used is experimental research with a pre-experimental research design with a one-group pretest-postest design. The sample taken was 29 students in class V SDN Gudang I. The instrument used was a written test in the form of description questions. The data analysis technique used in this study consists of a data normality test through the Lilliefors test and the t test. Based on the results of the t test data analysis, because the value of tcount = 17.591 and  ttable = 2.04841, with the testing criteria if tcount < ttable then H0 is determined. Which means that tcount is greater than ttable and is outside the H0 acceptance area, so H0 is rejected and H1 is accepted. So it can be concluded that the use of Problem Based Learning (PBL) model assisted by pop-up book media has a significant effect on students' mathematical problem solving ability on the perimeter and area of rectangles. Students' mathematical problem solving ability increased from the initial data of 11% to 100% in the final data.